(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The effect of commercial products of two neem seed extracts (Neem Azal-S and Margosan-O) on the predacious mites Amblyseius barkeri (Hughes) and Typhlodromus richteri Karg was studied. In spite of the fact that both Margosan-O and Neem Azal-S decreased eggs laying as well as the food consumption rate, both extracts at the two tested concentrations were considered to be safe for A. barkeri. Margosan-O can be considered harmless for T. richteri as no or only slight adverse effects were observed on the predator. Neem Azal-S seems to be harmful to T. richteri at 0.2% but slightly harmful at 0.05% concentration. The sex ratio of the progeny in both species was recorded.